Leviathan in Crisis - Franz Mauelshagen (Journal for the History of Environment and Society)
Long-term European experience with the plague and other epidemics has established a set of governance practices to limit the spread of disease, such as quarantine, lock-down of public life and reduction of economic activities etc. They have now returned during the COVID-19 crisis. However, it seems that the memory of European confrontations with pandemics has been lost among a majority of citizens. This has opened a door for social myths and conspiracy theories to enter the debate. Doubts about the legitimacy of restrictions on free movement (travel, social distancing) and individual choice (the wearing of masks) have been nourished particularly by the political right. Reviving our knowledge of past experiences with disease may be useful in this context. Tracing the history of the plague in Europe not only unveils a remarkable story of learning how to control the spread of a disease before its etiology was fully understood; it also reveals a co-evolutionary relationship between state power and disease, which is driven by the expansion of executive power into the area of public health. Returning to the present COVID-19 crisis, one can observe not only how the state of emergency is being used by autocrats and right-wing populists to undermine democratic institutions. One can also observe fatal government failure in countries like the United States, where trust in state power has been undermined by various groups in the recent past.